2020
DOI: 10.1186/s13045-020-00857-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: HNF4A-AS1/hnRNPU/CTCF axis as a therapeutic target for aerobic glycolysis and neuroblastoma progression

Abstract: Background: Aerobic glycolysis is a hallmark of metabolic reprogramming that contributes to tumor progression. However, the mechanisms regulating expression of glycolytic genes in neuroblastoma (NB), the most common extracranial solid tumor in childhood, still remain elusive. Methods: Crucial transcriptional regulators and their downstream glycolytic genes were identified by integrative analysis of a publicly available expression profiling dataset. In vitro and in vivo assays were undertaken to explore the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 66 publications
1
56
0
Order By: Relevance
“… Promoted HCC cell proliferation and metastasis [ 50 ] LIN28 mRNA transcription, mRNA translation Multiple tumors Let-7 family members, PD-L1 Upregulation Clinical samples of various tumor tissues Crosstalk between LIN28A/LIN28B and let-7 loops and certain oncogenes (such as MYC, RAS, PI3K/AKT, NF-κB, and β-catenin) to regulate the characteristics of cancer. LIN28/let-7/PD-L1 pathway Poor prognosis, increased cellular proliferation [ 51 , 52 ] HNRNPU Alternative RNA splicing, mRNA stability, mRNA metabolism mRNA transport Neuroblastoma HNF4A-AS1, CTCF Upregulation MCF 10A, HEK293T, NB cell lines HNF4A-AS1/hnRNPU/CTCF axis Promote aerobic glycolysis and NB progress [ 53 , 54 ]
Fig. 4 Signal pathways and metabolic pathways involved in abnormal RBP.
…”
Section: Introductionmentioning
confidence: 99%
“… Promoted HCC cell proliferation and metastasis [ 50 ] LIN28 mRNA transcription, mRNA translation Multiple tumors Let-7 family members, PD-L1 Upregulation Clinical samples of various tumor tissues Crosstalk between LIN28A/LIN28B and let-7 loops and certain oncogenes (such as MYC, RAS, PI3K/AKT, NF-κB, and β-catenin) to regulate the characteristics of cancer. LIN28/let-7/PD-L1 pathway Poor prognosis, increased cellular proliferation [ 51 , 52 ] HNRNPU Alternative RNA splicing, mRNA stability, mRNA metabolism mRNA transport Neuroblastoma HNF4A-AS1, CTCF Upregulation MCF 10A, HEK293T, NB cell lines HNF4A-AS1/hnRNPU/CTCF axis Promote aerobic glycolysis and NB progress [ 53 , 54 ]
Fig. 4 Signal pathways and metabolic pathways involved in abnormal RBP.
…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly and intriguingly, we discovered that RBMX protein mainly interacts with RNA-binding proteins, indicating that it may play an important role in cancer progression by regulating RNA splicing and processing [ 45 47 ]. For instance, hnRNP family proteins (hnRNP A1, I, K, and U) regulate tumor development and progression by mediating RNA splicing and processing [ 19 , 48 51 ]. In our study, 6 hnRNP proteins were found to interact with RBMX protein, suggesting that RBMX inhibited cancer progression by participating in the regulation of RNA splicing and processing.…”
Section: Discussionmentioning
confidence: 99%
“…High SLC2A1 expression correlates with poor prognosis in patients with surgically resected lung adenocarcinoma (LUAD), which suggests that SLC2A1 is a promising biomarker for LUAD (30). Song et al (31) found that HNF4A increased the expression of hexokinase 2 and SLC2A1, resulting in transactivation of CTCF and transcriptional alteration of HNF4A and other genes associated with tumor progression. Ding et al (32) discovered that miR-148b inhibited glycolysis in gastric cancer through targeting SLC2A1.…”
Section: Discussionmentioning
confidence: 99%